Spatiotemporal analysis for fighting COVID-19 in Iraq - Al-Bakri, Maythm (Geodesy and Cartography, 2022)
At the end of 2019, a new form of Coronavirus (later dubbed COVID-19) emerged in China and quickly spread to other regions of the globe. Despite the virus’s unique and unknown characteristics, it is a widely distributed infectious illness. Finding the geographical distribution of the virus transmission is therefore critical for epidemiologists and governments in order to respond to the illness epidemic rapidly and effectively. Understanding the dynamics of COVID-19’s spatial distribution can help to understand the pandemic’s scope and effects, as well as decision-making, planning, and community action aimed at preventing transmission. The main focus of this study is to investigate the geographic patterns of COVID-19 dissemination in Iraq from May 1 to July 29, 2021. The analysis was primarily based on using spatial analysis tools such as standard deviational ellipse (SDE) with in GIS environment, in addition to incidence rates calculations. The results revealed that the direction of COVID-19 spread is NW-SE. Furthermore, the findings showed that the rate of COVID-19 infections is greater at the middle and south of Iraq. This may aid decision-makers in identifying priority areas for emergency efforts.